2008
DOI: 10.1080/00048670802050579
|View full text |Cite
|
Sign up to set email alerts
|

‘Stealing Me from Myself’: Identity and Recovery in Personal Accounts of Mental Illness

Abstract: Objectives-To understand and promote recovery from serious mental illnesses, it is important to study the perspectives of individuals who are coping with mental health problems. The aim of the present study was to examine identity-related themes in published self-narratives of family members and individuals with serious mental illness. It adds to the body of research addressing how identity affects the process of recovery and identifies potential opportunities for using published narratives to support individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 38 publications
0
95
1
1
Order By: Relevance
“…Several scholars have analyzed such first-person accounts to discern common themes across recovery narratives. 16,21,22 A first theme emerging from these analyses is that recovery is routinely considered a process rather than an outcome-a deeply personal experience related to an individual's life aspirations. Saks 19 discovered that "I could be mentally ill and lead a rich and satisfying life."…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars have analyzed such first-person accounts to discern common themes across recovery narratives. 16,21,22 A first theme emerging from these analyses is that recovery is routinely considered a process rather than an outcome-a deeply personal experience related to an individual's life aspirations. Saks 19 discovered that "I could be mentally ill and lead a rich and satisfying life."…”
Section: Highlightsmentioning
confidence: 99%
“…These steps gather length and pace as recovery progresses, with Wisdom et al 21 describing a "striving for normalcy . .…”
Section: Highlightsmentioning
confidence: 99%
“…Whereas this could be interpreted as being incongruent with a qualitative methodology, we believe it was justified as a means of imposing an element of order on the search for narratives, especially because we were effectively faced with a sample of unknown size. Additionally, we did not want to introduce a sampling bias, as other researchers adopting similar approaches have, by restricting sampling to specific journals (Wisdom, Bruce, Saedi, Weis, & Green, 2008) or single Web sites (Headland, 2006 This strategy returned an overwhelming number of hits, most of which proved inappropriate on further investigation. This alerted us to the often erratic nature of electronic 6 searching and the need for careful consideration when entering search terms.…”
Section: Search Strategymentioning
confidence: 99%
“…Some authorities have suggested that researchers should not be required to seek review by an ethics committee or Institutional Review Board (IRB) when using material posted by individuals seeking public visibility (Frankel & Siang, 1999). Miles (2009) and Wisdom et al (2008) pointed out that their studies, using unsolicited narratives, were approved as exempt from institutional human subject protection requirements because they involved only the use of published or open source data. Robinson (2001) included a model for decision making regarding the need to pursue ethical approval when researching unsolicited narratives obtained from the Internet, but she omitted material obtained from personal Web sites.…”
Section: Requirement For Ethical Approvalmentioning
confidence: 99%
“…The onset of psychosis is therefore likely to significantly affect and possibly disrupt these natural processes in an individuals' life. Indeed, Wisdom, Bruce, Saedi, Weis and Green (2008) found that the onset of mental illness was associated with a loss of self or previously held identity, which needed to be overcome, or at the very least managed, to obtain hope for recovery. The onset of psychosis in an individual is also likely to occur during a critical period in a sibling's development (late adolescence to early adulthood) and therefore may also impact the course of the sibling's development.…”
Section: Introductionmentioning
confidence: 99%